Understanding the Law on Sexual Harassment in the Workplace (through a Case Law Lens): A Classic Fool’s Errand - Lux Lesley Kubjana (Obiter, 2020)
Sexual harassment at the workplace has become commonplace in South Africa, as is the case elsewhere in the world. International study that investigated the prevalence of sexual harassment at workplaces points that although it affects both men and women, most reported incidents portray women as more prone than men. Similar outlook is reflected in South Africa. The author is of the view that these numbers provide an opportunity to reflect and review the status quo insofar as regulation of sexual harassment is concerned. While this article acknowledges the general will to combat sexual harassment in South Africa, it raises concerns about both the regulation of and the interpretation of the sexual harassment regulatory framework. These two components do not seem to complement one another as they should. This is evident from a reading of the Code of Good Practice on the Handling of Sexual Harassment Cases, both in its original and amended form, which have leanings towards a subjective and guilt-presuming inquiry in the determination of what constitutes sexual harassment. Irreconcilable CCMA and court decisions bear testimony to this claim. First, the article argues that a subjective approach is susceptible to abuse and provides a breeding ground for more inconsistencies in sexual harassment jurisprudence. Moreover, individual perception cannot be determinative. Secondly, it bemoans the pattern by courts and the CCMA of overlooking the grammatical meaning of the words used in the Code of Good Practice. This article argues for the adoption of a pragmatic and objective approach based on facts and logic when dealing with sexual harassment at the workplace.